2007
DOI: 10.1002/ptr.2163
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of crude polysaccharides isolated from Solanum nigrum Linne on U14 cervical carcinoma bearing mice

Abstract: Solanum nigrum Linne (SNL) has been used in traditional Chinese medicine for centuries because of its diuretic and antipyretic effects. The present study examined the effect of the crude polysaccharides isolated from Solanum nigrum Linne (SNL-P) on tumor growth. SNL-P had a significant growth inhibition effect on cervical cancer (U14) of tumor-bearing mice. Further analysis of the tumor inhibition mechanism indicated that the number of apoptotic tumor cells increased significantly, the expression of Bax increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…The whole plant was dried in the shade and authenticated by Dr. J. C. Zhao at Hebei Normal University, China, where the herbarium voucher has been kept (E407). The method used for preparation of SNL-P is the same as we previously reported (Li et al, 2007). Briefly, dry SNL (500 g) was refluxed with petroleum ether (60-90 • C) to remove lipids, and then refluxed with 80% ethanol twice to remove monosaccharides and oligosaccharides.…”
Section: Preparation Of Snl-pmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole plant was dried in the shade and authenticated by Dr. J. C. Zhao at Hebei Normal University, China, where the herbarium voucher has been kept (E407). The method used for preparation of SNL-P is the same as we previously reported (Li et al, 2007). Briefly, dry SNL (500 g) was refluxed with petroleum ether (60-90 • C) to remove lipids, and then refluxed with 80% ethanol twice to remove monosaccharides and oligosaccharides.…”
Section: Preparation Of Snl-pmentioning
confidence: 99%
“…Lee and Lim (2006) reported 150 kDa glycoprotein isolated from SNL had a stimulatory effect on caspase-3 activation and PARP cleavage in HCT-116 cells, blocked nuclear factor-kappa B activation and reduced inducible nitric oxide (iNO) production. In our previous study, it was found that the crude polysaccharides isolated from SNL (SNL-P) could inhibit the growth of uterine cervical carcinoma (U14) in tumor models (Li et al, 2007). However, there is no report on which fraction of the SNL-P is the active component and whether its anti-tumor activity is correlated with its protective effects on the immune organ.…”
Section: Introductionmentioning
confidence: 99%
“…Although various parts of the S. nigrum plant contain polyphenols, gentisic acid, luteolin, apigenin, kaempferol, m-coumaric acid, anthocyanidin, their role in apoptosis is not clear. The crude polysaccharides from S. nigrum concomitantly up-regulates pro-appototic gene Bax and down-regulates Bcl-2 and mutant p53 gene expression in mice bearing cervical cancer (U14) 108 . On the other hand, pepsin and pancreatin digestion resistant peptide Lunasin has been claimed as a bioactive and bioavailable component due to inhibition of H3 and H4 acetylation and the phosphorylation of the Rb protein in mammalian cells and in a skin cancer mouse model 109 .…”
Section: 24mentioning
confidence: 99%
“…Solanum nigrum L. (SN) has been used in traditional folk medicine to treat different cancers. These findings indicate that SNE induced cell death in hepatoma cells via two distinct antineoplastic activities of SNE, the ability to induce apoptosis and autophagocytosis, therefore suggesting that it may provide leverage to treat liver cancer 159 . Solanum nigrum Linn.…”
Section: Issn: 0975-8232mentioning
confidence: 82%